Kajian Kolom Kuat Balok Lemah Pada Gedung Mall Pelayanan Publik Garut - Eko Walujodjati; Risdi Juanda (Institut Teknologi Garut, 2026)
The Garut Public Service Mall (MPP) building was established to provide convenience and efficiency to the public in the flexibility of doing business in Indonesia. The Garut MPP building is a reinforced concrete construction consisting of foundation structure, columns, beams, floor plates, stairs, and roof trusses. The beam-column connection determines the performance of the building structure, the principle of strong column weak beam is one of the parameters required in Earthquake resistant buildings. If structural failure is expected to occur in the beam not in the column. This research was conducted to determine the column-beam connection of the Garut Public Service Mall (MPP) Building meets the weak beam strong column principle and shear strength requirements. The research method used is quantitative method. Seeing the ultimate shear force is smaller than the nominal shear force, while the control column strong weak beam connection resultant column moment is greater than 1.2 resultant beam, column-beam connection there are 3 types, with type A (1 column 4 beams), type B (1 column 3 beams), type C (1 column 2 beams) control column-beam connection shear force type A obtained 1038. 5019 kN < 2448 kN, type B 519.251 kN < 1440 kN, type C 519.251 kN < 1440 kN, X-axis weak beam strong column control at type A connection obtained 436.4886 kN.m > 421.34 kN.m, type B 428.05 kN.m > 210.67 kN.m, type C 367.21 kN.m > 210.67 kN.m. The column-beam connection of the building has met the shear force control and weak beam strong column.